EXPLORATION OF THE DEVELOPING MARITIME TRANSPORTATION REGIONS OF INDONESIA - Riyadi, Muhammad (Jurnal Maritim Malahayati, 2024)
The islands in Indonesia can only be connected by sea routes between islands. Sea is not dividing, but uniting the various islands, areas and regions of Indonesia. Only through a nexus between the islands, between the beach, the unity of Indonesia can be realized. The cruise that connects the islands, was once the lifeblood of unifying the nation and the State of Indonesia. Cargo distribution is one of the biggest problems that slows down economic development in several regions, especially in eastern Indonesia. This creates a price differential between the two regions, with prices in the east being higher than in the west. In order to tackle this phenomenon, Indonesia government has launched several policies that are expected to force out economic equality for all regions especially and trigger the growth in peripheral area. The imbalance progress of regional development makes the sufficient infrastructure facility only available in western region especially in Java region. The propose of this articel is to identify government programs that are appropriate for the conditions of service gap in the sea transportation regions of Indonesia. The developing from peripheral regions, improving human quality life, and economic self-reliant becomes the foundation for the government to implement the Public Service Obligation project by issued the Sea-Toll Road program for reducing the economic disparity, inequality, and trigger the economic growth which characterized as a maritime country. However, in the implementation process, sea tollway programs face various challenges. Shipping of Short Sea Shipping (Coastal Shipping) as a backbone of national goods transportation has not realized.